From inflammation to healing: the crucial role of GPR91 activation and SDH inhibition in chronic diabetic wound recovery - Hengdeng Liu; Shixin Zhao; Hanwen Wang; Xuefeng He; Suyue Gao; Minmin Su; Miao Zhen; Shuying Chen; Lei Chen; Julin Xie (Stem Cell Research & Therapy)
Abstract Background Diabetic foot ulcers (DFU) typically exhibit impaired healing due to dysregulated re-epithelialization and excessive inflammation. Succinate, a key metabolic intermediate, is now understood to regulate inflammation through G Protein-Coupled Receptor 91 (GPR91) and succinate dehydrogenase (SDH), although its role in DFU remains unclear. Methods Co-cultures of M2 macrophages and epithelial cells, along with clinical samples, were used to analyze the expression of GPR91 and SDH. Functional assays were performed using high glucose (HG)-treated M2 macrophages (HG-M2) and an in vivo model. Cytokine and growth factor levels in cell supernatant were measured, and molecular mechanisms were explored via qRT-PCR, flow cytometry, and western blot analysis. Results Elevated glucose concentrations increased succinate levels and disrupted M2 macrophage–epidermal stem cells (EpSCs) interactions. GPR91 knockdown worsened HG-M2 dysfunction, while GPR91 overexpression (OE-GPR91) enhanced anti-inflammatory responses and reduced succinate. OE-GPR91-conditioned medium preserved EpSCs stemness and promoted migration mediated by hepatocyte growth factor (HGF). SDH inhibition (via Dimethyl malonate, DMM) boosted M2 macrophage activity by reducing reactive oxygen species (ROS) and upregulating Gpr91 expression. Mechanistically, GPR91 activated the pAkt/pGSK3β/β-catenin pathway, while DMM enhanced M2 macrophage function via the PI3K-Akt/pERK1/2 pathway. Conclusions GPR91 upregulation and SDH inhibition improve HG-M2 macrophage function, reduce inflammation, and enhance HGF-mediated EpSCs repair. Targeting both pathways may represent a promising approach to promote DFU healing.